Fixed duration vs. prolonged duration treatment after first line therapy in patients with systemic light chain amyloidosis. (2nd January 2022) - Rivera Duarte, Alfonso; Reece, Donna; Li, Xuan; Xu, Wei; Paul, Harminder; Masih-Khan, Esther; Winter, Andrew; Tiedemann, Rodger; Prica, Anca; Chen, Christine; Trudel, Suzanne; Kukreti, Vishal
Abstract: Background: The main objective of treatment in systemic light chain amyloidosis (AL amyloidosis) is to achieve the best hematological response. Deeper responses are associated with better organ responses and survival. In this study, we analysed the efficacy of prolonged duration treatment after first line in patients with AL amyloidosis. Methods: Retrospective analysis that included patients older than 18 years with AL amyloidosis. We excluded patients with more than 30% marrow plasmacytosis or concurrent multiple myeloma. Two cohorts identified accordingly if they received or not prolonged treatment after the first line. Survival analysis regarding progression free survival (PFS) and overall survival (OS) estimated with Kaplan–Meier and comparisons between groups with log-rank. Results: Thirty-eight patients were included in the analysis with a median age of 55 years. Twenty-one patients received prolonged duration treatment and 17 did not. In the prolonged duration group, after a median duration of 12 months, the median PFS was 58.8 months. In the fixed duration treatment group, PFS was 30.6 months. The difference was significant with p = .0045 favouring prolonged duration treatment. Organ response was sustained for a longer period in the prolonged duration treatment group. For OS, the difference was not significant. Conclusions: Prolonged duration treatment in patients with systemic light chain amyloidosis correlated with better PFS and deeper organ responses. Prospective studies are needed to analyse this further.